2022
DOI: 10.3390/ijms23179594
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intensity-Modulated Radiotherapy to the Head and Neck Region on the Oral Innate Immune Response and Oral Microbiome: A Prospective Cohort Study of Head and Neck Tumour Patients

Abstract: Neutrophils, also known as polymorphonuclear leukocytes (PMNs), form a significant component of the innate host response, and the consequence of the interaction between the oral microbiota and PMNs is a crucial determinant of oral health status. The impact of radiation therapy (RT) for head and neck tumour (HNT) treatment on the oral innate immune system, neutrophils in particular, and the oral microbiome has not been thoroughly investigated. Therefore, the objective of this study was to characterize RT-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In fact, it has been shown that IMRT for head and neck cancer can lead to dysbiosis of the oral microbiome. [ 4 , 5 , 26 ] Consequently, an oral dysbiotic state and direct insult from the effects of radiation therapy may increase the risk of highly morbid radiation-induced iatrogenic conditions such as oral mucositis and radiation-induced salivary hypofunction. Resultant shifts in the diversity and species richness of the oral microbiome composition as a consequence of irradiation could potentially allow for the emergence of putative pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been shown that IMRT for head and neck cancer can lead to dysbiosis of the oral microbiome. [ 4 , 5 , 26 ] Consequently, an oral dysbiotic state and direct insult from the effects of radiation therapy may increase the risk of highly morbid radiation-induced iatrogenic conditions such as oral mucositis and radiation-induced salivary hypofunction. Resultant shifts in the diversity and species richness of the oral microbiome composition as a consequence of irradiation could potentially allow for the emergence of putative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It has been established that IMRT for head and neck cancer can lead to dysbiosis of the oral microbiome. [ 4 , 5 ] Consequently, an oral dysbiotic state and direct insult from the effects of radiation therapy may increase the risk of highly morbid radiation-induced iatrogenic conditions such as oral mucositis and radiation-induced salivary hypofunction and xerostomia. Resultant shifts in the diversity and species richness of the oral microbiome composition as a consequence of irradiation could potentially allow for the emergence of putative pathogens, prolong oral mucositis, prolong acute and long-term oral toxicities, and predispose to oral infections with a risk of life-threatening bacteremia, often necessitating antimicrobials and prolonging in-patient hospitalization.…”
Section: Introductionmentioning
confidence: 99%
“…was reported in a case of oral cancer prior to radiotherapy, whereas Klebsiella and Pediococcus species as well as C. albicans were detected in the post-radiotherapy period (Anjali et al, 2020). In another prospective cohort study, it was observed that the number of commensal Gram-negative bacteria was reduced after exposure to radiation in the head and neck region (Mojdami et al, 2022). Schuurhuis et al investigated the changes in microbe composition depending on the methods of treatment (total patients n = 82; n = 29 surgical treatment, n = 26 intensive modulated radiation therapy, n = 27 intensive modulated radiation therapy in combination with chemotherapy) (Schuurhuis et al, 2016).…”
Section: Figurementioning
confidence: 92%
“…was reported in a case of oral cancer prior to radiotherapy, whereas Klebsiella and Pediococcus species as well as C. albicans were detected in the post-radiotherapy period ( Anjali et al., 2020 ). In another prospective cohort study, it was observed that the number of commensal Gram-negative bacteria was reduced after exposure to radiation in the head and neck region ( Mojdami et al., 2022 ). Schuurhuis et al.…”
Section: Radiotherapymentioning
confidence: 99%
“…During ulcerative mucositis progression, increased bacterial colonization at these sites causes unbalanced PAMPs and DAMPs, which trigger PRRmediated activation of downstream NF-κB signaling pathways, leading to augmented inflammatory responses due to the constant release of proinflammatory cytokines from innate immune cells [61]. The compositional changes to the oral microbiome observed across prior studies have varied, with reduction and expansion of differing microbial species being identified following treatment [71,72]. This varying nature of compositional analysis has led to suggestions that the resilience of the oral microbiome as well as the speed at which the microbial community is able to recover post-treatment may offer more reliable indicators for the impact of the oral microbiome on OM development and severity [73].…”
Section: Oral Microbiome-innate Immune Interactions and Om Developmentmentioning
confidence: 99%